Gallbladder Retrieval From Epigastric Versus Umbilical Port in Laparoscopic Cholecystectomy: A PRISMA-Compliant Meta-Analysis. (April 2020) - Mongelli, Francesco; La Regina, Davide; Zschokke, Irin; Ceppi, Marcello; Ferrario di Tor Vajana, Antonjacopo; Di Giuseppe, Matteo; Fischer, Henning; Heeren, Nickolaus; Metzger, Jürg; Gass, Markus
Purpose . To date, no evidence supports the retrieval of the gallbladder through a specific trocar site, and this choice is left to surgeons' preference. The aim of this meta-analysis was to investigate the influence of the trocar site used to extract the gallbladder on postoperative outcomes. Methods . According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a literature search of PubMed, Google Scholar, Cochrane Library, and EMBASE databases was performed. Terms used were: ("gallbladder" OR "cholecystectomy") AND "umbilical" AND ("epigastric" OR "subxiphoid"). Randomized trials comparing the gallbladder retrieval from different trocar sites were considered for further analysis. Results . Literature search revealed 145 articles, of which 7 matched inclusion criteria and reported adequate data about postoperative pain, operative time, port-site infections, and hernias. A total of 876 patients were included, and the gallbladder was extracted through epigastric or umbilical trocar site in 441 and in 435 patients, respectively. A statistically significant difference among groups was noted in terms of postoperative pain at 1, 6, 12, and 24 hours in favor of the umbilical trocar site ( P < .001). No significant differences were noted in postoperative hernia and infection rate, nor in terms of operative time. Conclusions . This meta-analysis shows a statistically significant reduction in terms of postoperative pain at 1, 6, 12, and 24 hours after surgery when the gallbladder is extracted through the umbilical port. Retrieval time, infections, and hernias rate implicate no contraindication for the choice of a specific trocar site to extract specimens. Despite limitations of this study, the umbilical trocar should be favored as the first choice to retrieve the gallbladder.